Management of dislocated transscleral fixated intraocular lens with one-side broken polypropylene suture - Basavaraj Tigari; Bruttendu Moharana; Mohit Dogra; Simar Rajan Singh; Ankur Singh; Bhukya Ravikumar; Ramandeep Singh (Indian Journal of Ophthalmology, 2020)
This video demonstrates the successful surgical technique for refixation of the same intraocular lens (IOL) by tying the same IOL to the sclera with the help of 9-0 polypropylene suture. A 62-year-old male patient presented with sudden loss of vision in the left eye. He had a history of undergoing transscleral fixation of intraocular lens (TSFIOL) using 10-0 polypropylene suture 13 years back for posttraumatic-dislocated nucleus. On examination, we noticed that he had IOL dislocation due to spontaneous breakage of suture of one of the haptic. The other haptic suture was intact. The long-term complication associated with TSFIOL procedure is breakage of the polypropylene suture leading to subluxation or dislocation of the IOL. We used closed-globe approach to successfully fixate the involved haptic of the same IOL. No intraoperative or postoperative complication was encountered in three such cases.